Synthesis of biodiesel from waste palm fatty acid distillate (PFAD) and dimethyl carbonate (DMC) via Taguchi optimisation method. (November 2021) - Esan, Akintomiwa O.; Olalere, Olusegun A.; Gan, Chee-Yuen; Smith, Siwaporn M.; Ganesan, Shangeetha
Abstract: The sustainability of the biodiesel production process is a controversial issue in terms of the production cost and promotion of a clean and safe energy process without adverse effects on the environment. Hence, the need to achieve energy sustainability is paramount due to the environmental benefits of biodiesel. In this study, a new approach was reported for biodiesel production from a cheap and readily available waste feedstock, palm fatty acid distillate (PFAD). An environmentally friendly green solvent, dimethyl carbonate (DMC), was utilised in the esterification of free fatty acids present in PFAD. The major influencing reaction parameters were optimised using the Taguchi (L9 ) orthogonal design, and statistical analysis was employed to determine the percentage contribution of the individual parameter on biodiesel yields. The maximum biodiesel yield of 89.50% was obtained at optimised reaction conditions, using the reaction time of 3.5 h, reaction temperature of 90 °C, DMC to PFAD molar ratio of 10:1 and catalyst concentration of 12 wt%. The percentage contribution of each of the individual parameters on the biodiesel yield was determined as follows: catalyst concentration (51.72%), reaction temperature (30.14%), DMC to PFAD molar ratio (16.94%), and reaction time (1.21%). The mechanism of esterification reaction between PFAD and DMC has also been proposed. This study illustrates that DMC can be successfully employed as an excellent methylating agent for the esterification of PFAD waste feedstock. The validation study also revealed a good agreement between the predicted and experimental values. Highlights: Biodiesel was produced from acidic palm fatty acid distillate (PFAD) feedstock. Dimethyl carbonate acts as a methylating agent in the conversion of free fatty acids. Esterification of free fatty acids present in PFAD using DMC to produce biodiesel. Taguchi method was used to optimise four vital esterification reaction parameters. The percentage contribution of each influencing parameter was estimated using ANOVA.